Philip Roth, Novels 2001-2007 – The Dying Animal, The Plot Against America, Exit Ghost (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2013)
Recensiamo il libro Roth, Philip. Novels 2001-2007 – The Dying Animal, The Plot Against America, Exit Ghost. Edited by Ross Miller. New York: The Library of America, 2013. Stampa.